1997
DOI: 10.1111/j.1471-0528.1997.tb11032.x
|View full text |Cite
|
Sign up to set email alerts
|

What changes in the organisation of cancer services will improve the outcome for women with ovarian cancer?

Abstract: Objective To examine the influence of operator specialty, volume of work and referral to an oncologist Design Population-based retrospective cohort study, using hospital records and Cancer Registry data.Setting The North Western Region, UK.Population Six hundred and ninety-one women undergoing laparotomy for histologically confirmed Methods Univariate and multivariate survival analyses.Main outcome measures Univariate survival estimates. Relative risks, derived from Cox's proportional hazards model, describing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 8 publications
3
31
0
Order By: Relevance
“…[6][7][8]10,[39][40][41][42][43][44] Recently, attention has focused on the potential for improved healthcare outcomes associated with concentration of cancer services in high-volume or expert centers. 45 A number of population-based studies have demonstrated conclusively that the surgical expertise and multidisciplinary care provided to patients with ovarian cancer at high-volume or expert centers are associated with superior survival outcomes compared with low-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8]10,[39][40][41][42][43][44] Recently, attention has focused on the potential for improved healthcare outcomes associated with concentration of cancer services in high-volume or expert centers. 45 A number of population-based studies have demonstrated conclusively that the surgical expertise and multidisciplinary care provided to patients with ovarian cancer at high-volume or expert centers are associated with superior survival outcomes compared with low-volume centers.…”
Section: Discussionmentioning
confidence: 99%
“…15 Cancer management by a multidisciplinary team improves the prognosis of ovarian cancer patients. 14,16,17 The Clinical Resource and Audit Group guideline states that patients who are suspected to have ovarian cancer should be referred in the first instance, either to a gynecological oncologist or to a gynecologist with a special interest in gynecological cancer. 18 Recommendations for centralization of ovarian cancer treatment have been given by The English National Health Service 19,20 and by the Society of Gynecological Oncologists in United States.…”
mentioning
confidence: 99%
“…Nearly a third (31%) of the patients were found to have a more advanced stage and 23 of these 31 patients (77%) had stage III disease. Other reports have pointed that specialization of the operating surgeons influence the patient's management and survival [5,[17][18][19][20]. Regarding our data about early EOC, it consistently shows serious deficiencies from the recommended standards of care.…”
Section: Discussionmentioning
confidence: 44%